Econometrical analysis of the purchasing power parity in Peru (2020)
Peru is a small economy open to the world, highly dependent on transactions with its trading partners that expose it to external shocks such as the financial crisis of 2008 or the shock of interest rates in 2006 that directly affect the behavior of the rate exchange. Therefore, the objective of this research was to contrast the validity of purchasing power parity between Peru and the United States in the period 2000-2019 from the functional forms of the parity equation in its absolute and relative forms. For the contrast analysis of cointegration relationships, the Johansen methodology was used; for the calculation of long-term parameters, the modification of autoregressive vector models. The results reveal that the purchasing power parity hypothesis for the Peruvian sol and for the US dollar is not fulfilled in any of its functional forms. This is due to the parameters estimated for absolute and relative parity being different from unity, thus rejecting the hypothesis of market efficiency in the long term for both Peru and the United States.